2005
DOI: 10.1103/physrevb.72.094418
|View full text |Cite
|
Sign up to set email alerts
|

Extinction of the Berezinskii-Kosterlitz-Thouless phase transition by nonmagnetic disorder in planar symmetry spin models

Abstract: The Berezinskii-Kosterlitz-Thouless (BKT) transition in two-dimensional planar rotator and XY models on a square lattice, diluted by randomly placed vacancies, is studied here using hybrid Monte Carlo simulations that combine single spin flip, cluster and over-relaxation techniques. The transition temperature Tc is determined as a function of vacancy density ρvac by calculations of the helicity modulus and the by finite-size scaling of the in-plane magnetic susceptibility. The results for Tc are consistent wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
75
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(88 citation statements)
references
References 46 publications
13
75
0
Order By: Relevance
“…They found that the apparent ill behavior obtained by Leonel et al [21] was a fake, probably due to a poor statistics. This was confirmed by other result [23]. We did a much more careful numerical study [25] using lattice sizes L × L, from L = 16 up to L = 1280, which is a much larger range than those used so far.…”
Section: Introductionsupporting
confidence: 84%
See 1 more Smart Citation
“…They found that the apparent ill behavior obtained by Leonel et al [21] was a fake, probably due to a poor statistics. This was confirmed by other result [23]. We did a much more careful numerical study [25] using lattice sizes L × L, from L = 16 up to L = 1280, which is a much larger range than those used so far.…”
Section: Introductionsupporting
confidence: 84%
“…This result is in flagrant disagreement with Refs. [22,23] and the Harris argument [18]. The work done by Young-Je et al [24] measuring the current-voltage in a site diluted Josephson junction arrays takes into account the quantum behavior of the system.…”
Section: Introductionmentioning
confidence: 99%
“…This issue is addressed in [35][36][37][38]. According to the Harris criterion, disorder does not change the leading scaling behaviour of a model if the critical exponent α associated with the specific heat of the pure model is negative [39].…”
Section: The Diluted Xy Modelmentioning
confidence: 99%
“…[14] To proceed, we attempt to locate the BKT transition temperature T c . Usually, T c can be determined by the finite-size magnetization and the helicity modulus in Fig.1, while in Fig.2 the peak of susceptibility is not used to locate T c for lack of accuracy, [14,18] and the peak of specific heat occurs a certain percent above T c . [19] The universal critical behavior of finite size induced magnetization, [4] …”
mentioning
confidence: 99%